1992
DOI: 10.1111/j.1365-2621.1992.tb08039.x
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Washing and Raw Material Source Affect Quality and Physicochemical Properties of Low‐salt, Low‐fat, Restructured Beef

Abstract: Five percent unwashed and washed skeletal (USM and WSM) and cardiac (UCM and WCM) muscle and fish surimi (FS) were evaluated in precooked (64.4 "C), restructured beef using 0.2% NaCl. Additionally, a 0.2% NaCl product without binder and a 1.0% NaCl treatment containing 5% USM were made. Washing enhanced sensory and instrumental texture measures of products containing CM but did not affect products containing SM. UCM and WCM appeared beneficial for maintenance of product color but tended to increase lipid oxida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0
1

Year Published

1993
1993
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 25 publications
1
35
0
1
Order By: Relevance
“…Our preliminary study comparing the oxidative stability of cardiac and skeletal muscle myofibrillar pellets showed that myofibrillar proteins isolated from beef heart developed rancidity much more rapidly than those from the skeletal muscle. This partially confirmed the observation by Kenney et al (1992) that washed cardiac muscle added to restructured beef was more prone to lipid oxidation and development of warmedover flavor compared to washed skeletal muscle.…”
Section: Introductionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our preliminary study comparing the oxidative stability of cardiac and skeletal muscle myofibrillar pellets showed that myofibrillar proteins isolated from beef heart developed rancidity much more rapidly than those from the skeletal muscle. This partially confirmed the observation by Kenney et al (1992) that washed cardiac muscle added to restructured beef was more prone to lipid oxidation and development of warmedover flavor compared to washed skeletal muscle.…”
Section: Introductionsupporting
confidence: 90%
“…Nuckles et al (1991) reported that washed beef heart, lung and spleen myofibrillar proteins formed self-support gels but both stress and strain (at failure) of the gels were less than those of skeletal myofibrillar gels. Monagle et al (1985) and Kenney et al (1992) showed that washed cardiac and skeletal muscle homogenates improved meat batter stability and textural attributes of restructured beef products, thus offering an alternative for increased utilization of animal byproducts.…”
Section: Introductionmentioning
confidence: 97%
“…To date, several studies have been conducted to evaluate the development of surimi-based products made from beef, pork, sheep and chicken (Antonomanolaki, Vareltzis, Georgakis, & Kaldrymidou, 1999;Kenney, Kastner, & Kropf, 1992;Nowasd, Kanoh, & Niwa, 2000;Park, Brewer, Novakofski, Bechtel, & McKkeith, 1996;Srinivasan & Xiong, 1996;Yang & Froning, 1992). The application of surimi technology in the production of surimibased products from other species could provide a new approach toward increasing its value and utilization.…”
Section: Introductionmentioning
confidence: 97%
“…It is defined as a refined fish protein product prepared by washing mechanically deboned fish to remove blood, lipids, enzymes and sarcoplasmic proteins, and as minced and washed fish flesh that has been stabilized by cryoprotectants (Vilhelmsson, 1997). Up until now, some studies conducted the development of surimi base products made from beef, pork and chicken (Kenney, Kastner, & Kropf, 1992;Park, Brewer, Novakofski, Bechtel, & McKeith, 1996;Srinivasan & Xiong, 1996;Yang & Froning, 1992). However, there is little information on effects of muscle types and washing times on qualities of surimi.…”
Section: Introductionmentioning
confidence: 98%